Antibacterial activity and phytochemical evaluation of the leaf root and stem bark extracts of parinari curatellifolia (planch. ex benth) - Chukwudi, Ugoh; Ayodeji, Fatokun; Amos, Jimba; olawunmi, Olajide (International Journal of Advanced Chemistry, 2014)
The different parts (leaf, root and stem bark) extracts of Parinari curatellifolia were studied to assess phytochemicals, antimicrobial activities and to confirm their traditional medicinal uses. Phytochemical screening of the crude extracts (leaf, root and stem bark) showed the presence of phenols, flavoniods, sterols, terpenoids, carbohydrates and saponnins. The crude extracts were screened for antimicrobial activity against three bacteria, Staphylococcus aureus, Streptococcus mutans and Lactobacillus spp. The minimum inhibitory concentration (MIC) of the methanol extract gave the highest zones of inhibition against the isolates used which revealed activities against S. aureus S. mutans and Lactobacillus spp. The biologically active methanol extract was purified using flash column chromatography. The two fractions (ME1 and ME2) were obtained from the column. Fraction ME1 gave the highest zone of inhibition ranging from 24±0.6 mm to 28±0.0 mm against S. mutans. This is significantly (P?0.05) different from the crude methanol extract with the zone of inhibition ranging from 23±0.00 mm to 26±0.90 mm. The activities of crude extracts were lower compared to that of the separated fractions. Keywords: Use about five key words or phrases in alphabetical order, Separated by commas.